RED MOLD RICE (ANGKAK) SEBAGAI MAKANAN TERFERMENTASI DARI CHINA: SUATU KAJIAN PUSTAKA - Kawuri, Retno (Jurnal Biologi Udayana; Vol 17 No 1 (2013): Jurnal Biologi, 2013)
Fermented food was produced in both traditional and modern techniques, to increase fungtional value and taste.  One example is Red Mold Rice (RMR) or Angkak, which is famous fermented rice from China. RMR was made from rice, red fungi Monascus purpureus and Monacolin as metabolit seconder, which believe can reduce Cholesterol dan trigelseride. Oral treatment with Cholestyn (1,2 g/d) can reduce LDL (bad cholesterol) up to 30,9% and triglesirida up to 34,1%, and can also increase HDL (good cholesterol) by 19,9%. Beside Monacolin, RMR also contains Cytrinin (0,2-122 mg/kg) which has a negative impact on functional and structural of human kidney and liver.
Keywords: Red Mold Rice, Monascus purpureus, Fermentation, Monacolin, Cytrinin